Hubungan Pemberian Reinforcement Orangtua dengan Perilaku Bullying pada Siswa SMP Perguruan Ksatrya Jakarta Pusat - Mustafida, Ika (Jurnal Kesehatan Holistic, 2019)
ABSTRACT Bullying is an aggressive action that continuous with the purpose to threatening and scaring other weak people. Awarding parental reinforcement can be expected to reduce bullying behavior. The purpose of this research is to determine the correlation between parental reinforcement with bullying behavior in junior high school students of Perguruan Ksatrya Jakarta. This research use descriptive crossectional design as a method and accidental sampling technique. As many as 190 samples in this research. This research analyzed with frequency distribution and chi square test. The results showed as many as 83 students (63,4%) who not behave bullying with positive reinforcement from their parents, and 48 students (36,6%) who behave bullying with positive reinforcement from their parents. In statistic test with confidence interval 95% and Alpha 0,05, obtained p value 0,034. It can be inferred that there is significant correlation between parental reinforcement with bullying behavior in junior high school students of PerguruanKsatrya Jakarta. The implication from this research is parents have to give positive reinforcement to adult to reduce bullying behavior